The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/joc.6746
|View full text |Cite
|
Sign up to set email alerts
|

Increased severe landfall typhoons in China since 2004

Abstract: Severe landfall typhoons (SLTYs), defined as those with maximum sustained wind speed ≥41.5 m s −1 at landfalls, strongly affect the coastal regions of China and cause grave losses of life and property. In this study, we analyse the SLTYs in China in peak summer (July-September) for the period of 1973-2017, during which typhoon landfall intensity (LFI) experienced significantly abrupt strengthening in 1987 and 2003. The period is divided into three subperiods: period-I (1973-1987), period-II (1988-2003), and pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 37 publications
(50 reference statements)
0
9
0
Order By: Relevance
“…Since the TC landfall numbers in southern and southeastern China are relatively stable from 1949 to the end of the twentieth century, track data before 1979, when satellites had not yet been widely available for TC observations, are not used. A transitional period from 1996 to 2001 is also excluded because the effect of the historically massive 1997/98 El Niño event, which has been reported to have an unusual impact on the TC activities over the WNP ocean basin in this period (Iizuka and Matsuura 2008;Liu and Chan 2018;Wu et al 2018;Balmaseda et al 2013;Yao et al 2020). To confirm the robustness of the results on the differences of TC track density over the WNP before and after the abrupt change at the end of twentieth century, we evaluated the deviation caused by a slightly different choice of the dividing year for the two stages.…”
Section: Phenomena a Overall Trendmentioning
confidence: 99%
“…Since the TC landfall numbers in southern and southeastern China are relatively stable from 1949 to the end of the twentieth century, track data before 1979, when satellites had not yet been widely available for TC observations, are not used. A transitional period from 1996 to 2001 is also excluded because the effect of the historically massive 1997/98 El Niño event, which has been reported to have an unusual impact on the TC activities over the WNP ocean basin in this period (Iizuka and Matsuura 2008;Liu and Chan 2018;Wu et al 2018;Balmaseda et al 2013;Yao et al 2020). To confirm the robustness of the results on the differences of TC track density over the WNP before and after the abrupt change at the end of twentieth century, we evaluated the deviation caused by a slightly different choice of the dividing year for the two stages.…”
Section: Phenomena a Overall Trendmentioning
confidence: 99%
“…In this study, we only applied the data over the satellite era from 1980 to 2019 when TC data were relatively reliable. Moreover, we focused on the TC activity during peak summer (July-September, JAS) over the WNP (100 • E-180 • , north of the equator), because it is the active TC season for southern China (Zhang et al 2019, Yao et al 2021. To reduce the effect of global warming, we removed the long-term linear trend of the monthly reanalysis data.…”
Section: Methodsmentioning
confidence: 99%
“…From the annual-mean perspective, the significant poleward and landward migration of TC activity in the past 40 years have been reported, increasing the coastal TC risk of China (Kossin et al 2014, Wu et al 2015, Sharmila and Walsh 2018, Wang and Toumi 2021. In particular, the annual frequency and intensity of the TCs making landfall in southern China exhibit an upward trend during the last decades (Liu and Chan 2018, Shan and Yu 2021, Yao et al 2021. Thus, an improved understanding of the variability of TC activity over southern China is both scientifically and socially important.…”
Section: Introductionmentioning
confidence: 99%
“…The rapid development of the Chinese economy has resulted in an increase in the population of coastal areas, which has increased their vulnerability and socio‐economic losses over the past decades (Zhang et al, 2009). Furthermore, activities of the landfalling TCs in China also display striking variability under climate change (Li et al, 2017; Yao et al, 2021). Previous studies suggested that the damaging potential of the TCs in China shows an increasing trend due to their increased mean duration and intensity at landfall (Li et al, 2022; Shan & Yu, 2021).…”
Section: Introductionmentioning
confidence: 99%